Influence of gender on periodontal outcomes: A retrospective analysis of eight randomized clinical trials - Castro Dos Santos, Nidia; Westphal, Miriam R.; Retamal-Valdes, Belen; Duarte, Poliana Mendes; Figueiredo, Luciene Cristina; Faveri, Marcelo; Shibli, Jamil; Soares, Geisla; Miranda, Tamires; Fermiano, Daiane; Borges, Ivan; Goncalves, Cristiane; et al. (Journal of periodontal research, 2024)
AIMS: To explore the influence of gender on periodontal treatment outcomes in a dataset of eight RCTs conducted in Brazil, United States, and Germany. - METHODS: Clinical parameters were compared between men and women with stages III/IV grades B/C generalized periodontitis at baseline and 1-year post-therapy, including scaling and root planing with or without antibiotics. - RESULTS: Data from 1042 patients were analyzed. Men presented a tendency towards higher probing depth (p = .07, effect size = 0.11) and clinical attachment level (CAL) than women at baseline (p = .01, effect size = 0.16). Males also presented statistically significantly lower CAL gain at sites with CAL of 4-6 mm at 1-year post-therapy (p = .001, effect size = 0.20). Among patients with Grade B periodontitis who took antibiotics, a higher frequency of women achieved the endpoint for treatment (i.e., ≤4 sites PD ≥5 mm) at 1 year than men (p < .05, effect size = 0.12). - CONCLUSION: Men enrolled in RCTs showed a slightly inferior clinical response to periodontal therapy in a limited number of sub-analyses when compared to women. These small differences did not appear to be clinically relevant. Although gender did not dictate the clinical response to periodontal treatment in this population, our findings suggest that future research should continue to explore this topic.
Gesehen am 28.03.2025